The Impact of Silozi Language on the Teaching of Numeracy in the Zambezi Region - M Mukwambo; D Mhakure; N Sitwala (International Journal of Trends in Mathematics Education Research, 2020)
The study reports on the challenges lower primary numeracy teachers in the Zambezi Region face when using Silozi language as a medium of instruction. The use of Silozi language as a medium of instruction is part of the Namibian language policy in schools. In the Zambezi Region, Silozi, a lingua franca is considered predominant. The findings of the study show that teachers were unable to interpret the concepts in the curriculum and learners could not express their ideas using the lingua franca. However, when Numeracy questions were presented to the learners in symbolic form and in their mother tongue, they did not face challenges in understanding the questions. The study uses the socio-cultural theory as theoretical framework.